PERANAN MARKER JANTUNG SEBAGAI PENANDA KEBERHASILAN TERAPI GAGAL JANTUNG AKUT - Prima Ursila; Muhammad Stukri (Universitas Fort De Kock, 2020)
Acute heart failure is a term used to describe the condition of heart failure with acute onset and worsening of symptoms and signs of heart failure. Acute heart failure is associated with decreased survival and high rehospitalization. In addition to routine clinical laboratory tests, a number of biomarkers have received recommendation helping in prognostic acute heart failure. Biomarkers must have underlying pathophysiological relevance, and if the prognostic should be used both to initiate certain therapies and monitors during the therapy of acute heart failure.